The academic foundations of interpreting studies - Roy, Cynthia B (Gallaudet University Press, 2018)
Contents -- Preface -- Acknowledgments -- The discipline of interpreting studies -- Through the lens of history -- Through the lens of translation -- Through the lens of linguistics -- Through the lens of sociology and anthropology -- Through the lens of social psychology -- Through the lens of cognitive psychology -- Applying the lenses -- References -- Index.